2002
DOI: 10.1007/s00284-002-3704-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth-Promoting Pseudomonas putida WCS358 Produces and Secretes Four Cyclic Dipeptides: Cross-Talk with Quorum Sensing Bacterial Sensors

Abstract: The most universal cell-cell signaling mechanism in Gram-negative bacteria occurs via the production and response to a class of small diffusible molecules called N-acylhomoserine lactones (AHLs). This communication is called quorum sensing and is responsible for the regulation of several physiological processes and many virulence factors in pathogenic bacteria. The detection of these molecules has been rendered possible by the utilization of genetically engineered bacterial biosensors which respond to the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
140
2
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(147 citation statements)
references
References 13 publications
2
140
2
3
Order By: Relevance
“…This regulatory mechanism is known as quorum sensing, and it can be mediated by different signal molecules. In most gram-negative bacteria where it has been described, it is mediated by AHLs, although other molecules such as quinolones or cyclic dipeptides also act as quorum-sensing signals (11,29). AHLs are found in different bacteria and regulate processes such as bio- (33).…”
Section: Discussionmentioning
confidence: 99%
“…This regulatory mechanism is known as quorum sensing, and it can be mediated by different signal molecules. In most gram-negative bacteria where it has been described, it is mediated by AHLs, although other molecules such as quinolones or cyclic dipeptides also act as quorum-sensing signals (11,29). AHLs are found in different bacteria and regulate processes such as bio- (33).…”
Section: Discussionmentioning
confidence: 99%
“…A number of DKPs, including cyclo(L-Tyr-L-Pro) and cyclo(LPhe-L-Pro), have been detected in culture supernatants from a variety of Gram-negative bacteria, such as Pseudomonas spp., Vibrio spp., Proteus mirabilis, Citrobacter freundii, and Enterobacter agglomerans, and they have been shown to modulate quorumsensing systems that commonly respond to acyl-homoserine lactone signaling molecules (26,27,45). Similarly, it was found that Gram-positive Lactobacillus plantarum species also produced cyclic dipeptides, including cyclo(L-Phe-L-Pro), cyclo(L-Phe-trans-4-OH-L-Pro), and cyclo(Gly-L-Leu), which exhibited antifungal activity (28,46).…”
Section: Discussionmentioning
confidence: 99%
“…(301) and Gram-negative (302,303) species produce DKPs and appear to be capable of targeting LuxR proteins in engineered biosensors, but they were also found to affect S. liquifaciens swarming (303). The oral pathogen Streptococcus mutans utilizes multiple peptidebased quorum-sensing systems that promote bacteriocin production, competence, and biofilm development.…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%